Knowledge of persons with visual impairment and typically developing persons about sexually transmitted diseases - Stekić, Dunja (Specijalna edukacija i rehabilitacija, 2022)
Introduction. Sexually transmitted diseases are a public health, medical and social problem. They are among the five most common diseases in the world. Knowledge about sexually transmitted infections and protection from them is one of the most important methods of prevention and protection of sexual and reproductive health. Objectives. The main aim of this paper was to determine the knowledge of persons with visual impairments about sexually transmitted diseases. Other objectives included determining the differences between knowledge of persons with and without visual impairments about sexually transmitted diseases and determining gender, age, and educational differences. Methods. The study included 50 participants with visual impairment and 50 participants without visual impairment, equal in gender, age, and level of education. Data were collected online in May 2020. The Illustrative Questionnaire for Interview-Surveys with Young People was used for this purpose. Results. The main results showed a statistically significant difference between persons with and those without visual impairment in terms of knowledge about the types of sexually transmitted diseases. In the subsample of participants with visual impairment, there were statistically significant differences related to gender, but no age and educational differences. Conclusion. It is necessary to pay more attention to people with visual impairment with regard to sexual and reproductive health through the organization of training and workshops in order to increase knowledge on this topic.